Antimicrobial and enzymatic potential of Pterocarpus erinaceus Poir. endophytes used in Benin (West Africa) - Sophia Aliou; Brice Fanou; Jean Robert Klotoé; Eric Agbodjento; Victorien Dougnon; Norbert Gbesso; Toussaint Yangambele; Curiace Hinnilo; Toussaint Sovègnon; Remi Akotègnon; Alda Yemadje; Guevara Nonviho; et al. (Bulletin of the National Research Centre)
Abstract Background Pterocarpus erinaceus Poir. is a plant widely used in traditional medicine in Benin, treating various diseases such as diabetes, ulcers, parasitic infections, hypertension, and infertility. This plant is under strong anthropogenic pressure due to its overexploitation, putting it in danger of extinction. The study aims to explore the antimicrobial and enzymatic activities of endophytes produced by Pterocarpus erinaceus. Methods Fresh leaves, stems, and roots of P. erinaceus, collected in two phytogeographical zones of Benin, Savalou and Abomey-Calavi of Benin, were sterilized to eliminate surface microorganisms prior to cultivation and isolation of endophytes. Isolated endophytes were tested for various enzymatic activities (catalase, cellulase, protease, lipase, and amylase), and their antimicrobial activities were evaluated by measuring inhibition diameters. The content of total polyphenols and flavonoids was determined by spectrophotometry. Results The results showed that bacterial endophytes have a higher colonization (80.55%) and isolation (69.44%) rates than fungal endophytes (44.44% and 50%, respectively). Bacterial endophytes expressed more enzymatic activities such as lecithinase and amylase, whereas fungal endophytes showed little. Only two fungal isolates (HT1a and HF2b) showed antibacterial activity, and one isolate (HF2b) showed antifungal action against Candida albicans, while no bacterial isolate demonstrated significant antimicrobial activity. Fungal isolates show significant variation in polyphenol content, while bacterial isolates show similar levels. As far as flavonoids are concerned, bacterial strains such as F3b and SR2C have high levels, unlike fungal endophytes which contain very few. Conclusion These results underscore the importance of conserving P. erinaceus while exploring its endophytes for potential therapeutic applications.